Satisfaction and perceived usefulness of a boxing group exercise class at the Parkinson Patient Association - Godinho, Catarina (2022)
Poster apresentado no Congresso Anual da Sociedade Portuguesa de Doenças do Movimento (SPDMov), Curia, 15-16 de Março 2019